2016
DOI: 10.1016/j.jadohealth.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating College Students' Displayed Alcohol References on Facebook and Twitter

Abstract: Purpose Current trends suggest adolescents and young adults typically maintain a social media “portfolio” of several sites including Facebook and Twitter, but little is known regarding how an individual chooses to display risk behaviors across these different sites. The purpose of this study was to investigate college students’ displayed alcohol references on both Facebook and Twitter. Methods Among a larger sample of college students from two universities, we identified participants who maintained both Face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 28 publications
1
38
0
1
Order By: Relevance
“…Given the public nature of these Tweets, it is important to note that they may serve to normalize blacking out as a consequence of drinking (or as the aim of a drinking). There is a substantial body of literature highlighting that individuals (particularly young adults) drink according to their perception of others’ drinking (Borsari and Carey, ) and a number of studies have highlighted that exposure to or engagement with alcohol‐related content on social networking sites may influence behavior (Boyle et al., ; Curtis et al., 2018a,b; Moreno et al., ; Steers et al., ). Thus, exposure to preblackout drinking Tweets may affect an individual's perception of blacking out as a normal consequence of drinking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the public nature of these Tweets, it is important to note that they may serve to normalize blacking out as a consequence of drinking (or as the aim of a drinking). There is a substantial body of literature highlighting that individuals (particularly young adults) drink according to their perception of others’ drinking (Borsari and Carey, ) and a number of studies have highlighted that exposure to or engagement with alcohol‐related content on social networking sites may influence behavior (Boyle et al., ; Curtis et al., 2018a,b; Moreno et al., ; Steers et al., ). Thus, exposure to preblackout drinking Tweets may affect an individual's perception of blacking out as a normal consequence of drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the public nature of social networking websites, they are a common outlet for individuals to discuss substance use (Boyle et al., ; Egan and Moreno, ; Griffiths and Casswell, ; Moreno et al., ). For example, a study of 11,236 university students found that 97% used social networking websites and that 71% of these students reported posting alcohol‐related content (Erevik et al., ).…”
Section: Alcohol‐related Blackoutsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that, compared with nondisplayers and alcohol displayers (who posted about alcohol but not about getting drunk), those who displayed intoxication or problematic drinking on their Facebook scored higher on the AUD identification test (AUDIT), and their average AUDIT level was considered risky according to the national standard; a finding confirmed by Ridout, Campbell, and Ellis (2012). Twitter is also used to display alcohol references; about one third of college students who tweet frequently were found to share alcohol-related content (Moreno, Arseniev-Koehler, Litt, & Christakis, 2016).…”
Section: Twitter: the 140 Characters To Get You Drunkmentioning
confidence: 99%
“…For instance, social media analytics were used to increase the e ciency of the health sector in different ways (Paul & Dredze, 2014). Some of the examples include: (a) Predictions-related to non-contagious diseases, e.g., heart disease mortality using psychological language used in tweets (Eichstaedt et al, 2014); (b) Predictions-related to contagious diseases, e.g., the use of tweets to evaluate the disease activity and the US public perceptions during the in uenza H1N1 pandemic (Signorini et al, 2011); (c) Governance in health, e.g., adapting social media in local health departments (Harris et al, 2013); (d) Awareness raising, e.g., health information dissemination through social networks (Scanfeld et al, 2010); (e) Study on non-healthy addictions, e.g., college student's addiction to alcohol using Facebook and Twitter posts (Moreno et al, 2016); (f) Student education in the health sector, e.g., importance in introducing social media analytics to nursing curriculum (Jones et al, 2016), and; (g) Healthcare professionals-related issues, e.g., women in the health sector (Devi, 2015). Nevertheless, the use of social media analytics to increase the e ciency of community centric policy decisions during a pandemic is still an understudied area of research.…”
Section: Social Media Analyticsmentioning
confidence: 99%